The Efficacy and Safety of Janus Kinase Inhibitors for Patients With COVID-19: A Living Systematic Review and Meta-Analysis - Zhang, Xueyang; Shang, Lianhan; Fan, Guohui; Gu, Xiaoying; Xu, Jiuyang; Wang, Yeming; Huang, Lixue; Cao, Bin (Frontiers in Medicine, 2022)
Background Cytokine storm observed in patients with severe Coronavirus Disease 2019 (COVID-19) contributes to poor clinical outcomes and increased mortality. Janus kinases (JAKs) are important mediators in the cytokine storm. Therefore, we conduct a living systematic review and meta-analysis of the literature investigating efficacy and safety of JAK inhibitors for patients with COVID-19. Methods Databases were searched up to December 1, 2021 for interventional and observational studies comparing JAK inhibitor treatment with concurrent control in patients with COVID-19. Efficacy and safety outcomes were evaluated by pooled risk ratio (RR). Results Of 3,170 records retrieved, 15 studies were eligible and 13 were evaluated in the meta-analysis (n = 3,977). Based on data from three randomized controlled trials (RCTs), baricitinib treatment significantly decreased mortality by day 28 in hospitalized patients with COVID-19 (RR = 0.64, 95% CI 0.51–0.80) without increasing the incidence of adverse outcomes. In subgroup analysis, patients who required supplemental oxygen (RR = 0.62, 95% CI 0.41–0.95) or high-flow oxygen/non-invasive ventilation (RR = 0.59, 95% CI 0.42–0.85) at baseline benefited most. Pooled analysis of all eligible studies for JAK inhibitors (baricitinib, ruxolitinib, tofacitinib, and nezulcitinib) demonstrated a significant decrease in mortality (RR = 0.62, 95% CI 0.49–0.78) with no increase in the risk of adverse events. Conclusion Baricitinib probably decreases mortality in hospitalized adult patients with COVID-19, especially for patients who required supplemental oxygen or high-flow oxygen/non-invasive ventilation at baseline. The efficacy and safety of other JAK inhibitors, such as ruxolitinib, tofacitinib, and nezulcitinib, await more evidence. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021261414, identifier: CRD42021261414.